Analysis of Credit Utilization Among Street Vendors in Ruteng City - Felisia Saron Tjengga; Fransina W. Ballo; Maria Indriyani Hewe Tiwu (Formosa Journal of Sustainable Research, 2023)
The purposive of this research is to determine the use of credit taken by street vendors in Ruteng city which they take from BRI bank and to find out the reasons they take credit from BRI bank. The method for determining the research informants uses a purposive method. The data collection methods used consisted of: interviews, and observations and documents. The data analysis used is descriptive analysis with a qualitative approach. The object of this research is the use of credit by street vendors in the city of Ruteng around the location of the Ruteng Regional Hospital and UNIKA Santu Paulus Ruteng. These utilization interests are divided into 3 interests, namely for production, consumption and investment purposes. First, for production purposes, namely to fulfill and increase business capital for trading, a means to make business activities smoother and business performance better than before, expanding business and work opportunities. Second, for consumption purposes, namely meeting personal consumption needs such as paying children's school fees, house rental costs, house renovation costs. Third, for investment purposes, namely to buy jewelry and buy a motorbike